WEBINAR TENTANG HUKUM PERLINDUNGAN KONSUMEN DI SMA PELANGI KASIH (AMAN BELANJA ONLINE) - Gunardi Gunardi; Andryawan Andryawan; Olivia Pauline Hartanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
In today's adult era, lots of buying and selling agreements occur in both the physical market and the digital market was carried out. The people who make these transactions are not limited to adults but start from children to the elderly. However, problems arise because there are still not many people who realize that in the case of the transaction being carried out there is a consumer protection law that regulates the rights and obligations of each party. This is also felt by Class XII students and teachers from Pelangi Kasih High School who still have very little knowledge in the field of consumer law. On this matter, the author aims to determine the extent of knowledge and awareness of Class XII students and teachers of SMA Pelangi Kasih on consumer protection. The method is carried out by providing direct online discussions through the zoom application which is divided into material presentation sessions and question-and-answer sessions. Related to the implementation of the activity, the materials included in the discussion of this activity can be described, in general explaining related to consumer protection, standard clauses, dispute resolution methods, several case examples and some tips for safe online shopping. The conclusion obtained is that the awareness and knowledge of Class XII students and teachers of SMA Pelangi Kasih regarding Consumer Protection Law is still low so that the implementation of this activity is expected to provide an awareness of the rights that a consumer needs to obtain.